Implementasi Al-'Arabiyah li an-Nāṭiqīna bi al-Indūnīsiyyah (ALBI) dalam Pembelajaran Bahasa Arab - Muchammad Nur Huda (STIQ Amuntai, 2025)
This study aims to describe the implementation and supporting and inhibiting factors of the application of Al-'Arabiyah li an-Nāṭiqīna bi al-Indūnīsiyyah (ALBI) in Arabic language learning. This study uses a qualitative descriptive approach with data collection methods in the form of observation, in-depth interviews, documentation, and triangulation. The results of the study indicate that the implementation of ALBI is part of the reformulation of the Foreign Language Development Program (P2KBA) in intensive Arabic language learning to improve students' linguistic competence, which includes aspects of istimā', kalām, qirā'ah, and kitābah. This program is implemented twice a week with various learning methods and strategies and uses Al-'Arabiyah li an-Nāṭiqīna bi al-Indūnīsiyyah (ALBI) materials. Supporting factors for the success of this implementation include instructor competence, availability of teaching materials, and learning evaluation through the Final Online Test (FOT). Meanwhile, inhibiting factors include limited technological infrastructure, heterogeneity in student backgrounds, and suboptimal utilization of digital platforms. These findings indicate that despite significant progress, the optimization of ALBI implementation still requires improvement in various supporting aspects.